Mixing chaotic maps and electromagnetic interference reduction - de Micco, Luciana (2012)
Spread-spectrum techniques for improving Electromagnetic Compatibilities are investigated. This requires generating Constant Envelope Wideband signals. We produce them via chaotic maps that yield pseudo random time series, used afterwards to modulate sinusoidal waves in frequency. How to assess a maps´s suitability for such task is also discussed.